Clinical status in adolescents: is its impact on oral health‐related quality of life influenced by psychological characteristics?. (28th March 2013) - Foster Page, Lyndie A.; Thomson, W. Murray; Ukra, Ali; Baker, Sarah R.
Abstract : The objective of this study was to examine, using structural equation modelling, the relationships among clinical characteristics (such as caries experience and malocclusion), oral health‐related quality of life (OHRQoL), and psychological characteristics (mental health, self‐esteem, somatisation, and social perception of body image) in adolescents in New Zealand. Adolescents were examined for malocclusion using the Dental Aesthetic Index (DAI) and for dental caries. Among the 353 (58.8%) 12‐ and 13‐yr‐old adolescents who took part in this cross‐sectional study, the overall mean ± SD decayed, missing, or filled surfaces (DMFS) value was 1.6 ± 3.0, with slightly more than 50% of being caries‐free; the mean ± SD DAI was 31.5 ± 7.6, with one‐quarter of subjects having a 'handicapping' malocclusion. The structural equation modelling analysis showed that the structural model was a good fit to the data. As hypothesized, the DAI score significantly predicted OHRQoL. There was no direct relationship between caries experience (DMFS) and OHRQoL, but there was an indirect effect of DMFS on OHRQoL mediated through psychological characteristics. The amount of OHRQoL variance accounted for in the model was substantial, at 62%. It appears that investigating OHRQoL in adolescents is not straightforward; while malocclusion directly affects OHRQoL, the influence of dental caries experience is less direct.